The Role of Large Mammals as Vitamin C Sources for MIS 3 Hominins - Guil-Guerrero, José Luis (Quaternary, 2023)
The acquisition of large prey by hominins living during the Marine Isotope Stage 3, including Neanderthals and Anatomically Modern Humans, had nutritional and bioenergetic implications: these contain high fat amounts, provide a high energy return, and the strategies and skills required to acquire small prey were different from those required to acquire the former. Vitamin C availability at several MIS 3 periods could have had a strong seasonal variability and would have been decisive for hominin groups’ survival. During the cold periods of the MIS 3, Paleolithic hominins had variable available amounts of vitamin C-containing plants only in the short summers, and for the remainder of the year, viscera would have been their best source of vitamin C. Meanwhile, the dependence on small mammals could have caused an erratic distribution of viscera to be consumed by such hominins, thus leading to chronic scurvy, and compromising their survival. Then, the hunting of large mammals would have helped to meet the daily vitamin C needs, besides an efficient energy supply. Therefore, the decline of large prey during the MIS 3 could have been critical for hominins survival, and thus the efficient exploitation of alternative vitamin C-rich food resources such as birds and aquatic animals could have favored the evolutionary success of hominin populations.